Hubungan Antara Karakter Klinikopatologik dengan Grup Prognostik WHO pada Pasien Gastrointestinal Stromal Tumor di RSUP Dr. Mohammad Hoesin, Palembang - Nur Azizah; Suly Auline Rusminan; Subandrate (Majalah Patologi Indonesia, 2021)
BackgroundGastrointestinal stromal tumors are the most common mesenchymal tumors in the gastrointestinal tract. Based on tumor size andmitotic index, WHO classified GIST into three prognostic groups which were benign, uncertain malignant potential, and malignant.Some studies revealed that there was variation in association between age, gender, tumor location, histopathologic type and prognosisof GIST patients. This study aimed to identify and analyze the association between clinicopathologic characteristics and WHOprognostic group in GIST patients at RSUP Dr. Mohammad Hoesin Palembang.MethodsThis study used 30 medical records of GIST patients during 01 January 2014 to 27 December 2018 in the Department of AnatomicPathology RSUP Dr. Mohammad Hoesin. Clinicopathologic characteristics and WHO prognostic group data were collected. Theassociation between clinicopathologic characteristics (age, gender, tumor location, histopathologic type) and WHO prognostic groupwere analyzed by chi-square test.ResultsFrom 30 subjects, 40% of the patients aged 52-58 years.There was no gender predilection. A total of 33.3% of the GISTs were locatedin the small intestine. Majority of histopathologic type was spindle cell type (93.3%). Bivariate analysis showed there were no significantassociation between clinicopathologic characteristics: age (p=0.811), gender (p=0.682), tumor location (p=1.000), histopathologic type(p=0.469) and WHO prognostic group.ConclusionThere was no significant association between clinicopathologic characteristics and WHO prognostic group in GIST patients at RSUPDr. Mohammad Hoesin Palembang. We suggest doing a cohort study about association between clinicopathologic characteristics andsurvival rate in GIST patients.